2017
DOI: 10.1111/liv.13536
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm of Golgi protein 73 and liver stiffness accurately diagnoses significant fibrosis in chronic HBV infection

Abstract: Serum GP73 is a robust biomarker for significant fibrosis diagnosis. GP73-LS algorithm provided better diagnostic accuracy than currently available approaches. More than 60% antiviral naïve CHB patients could use this algorithm without resorting to liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…However, it should be noted that just as other tests, such as LS, APRI and FIB‐4, the diagnostic accuracy of serum GP73 was influenced by the magnitude of intrahepatic inflammation which renders this biomarker less accurate in CHB patients. Therefore, strategies such as combining different tests with serum GP73 might improve the overall accuracy . Moreover, the importance of serum GP73 as a predictor of fibrosis was substantially reduced in patients with ongoing antiviral therapy compared with antiviral‐naïve patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it should be noted that just as other tests, such as LS, APRI and FIB‐4, the diagnostic accuracy of serum GP73 was influenced by the magnitude of intrahepatic inflammation which renders this biomarker less accurate in CHB patients. Therefore, strategies such as combining different tests with serum GP73 might improve the overall accuracy . Moreover, the importance of serum GP73 as a predictor of fibrosis was substantially reduced in patients with ongoing antiviral therapy compared with antiviral‐naïve patients.…”
Section: Discussionmentioning
confidence: 98%
“…Such diagnostic performance suggested that it is not accurate enough for clinical practice, using serum GP73 alone. Thus, a combination strategy is needed to optimize the application of serum GP73 in selected patients …”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to point out that the study by Cao and co‐workers looked at a relatively “healthy” population of HBV‐infected patients, in which this GP73‐LS algorithm was developed, applied and validated. About half of the patients had no significant fibrosis at all, and ALT levels were within normal range or only mildly elevated . It is therefore difficult to rule out necro‐inflammation as a confounding factor for GP73 levels based on this cohort, especially since inflammation had been demonstrated to affect GP73 levels in a prior study .…”
mentioning
confidence: 87%
“…In this issue of Liver International , Cao and colleagues demonstrate that Golgi protein 73 (GP73) correlated with histologically proven liver fibrosis, independent of hepatic inflammation or comorbidities, in a large cohort of treatment‐naïve chronic HBV‐infected patients. They propose a novel algorithm, tested and validated in two cohorts, in which GP73 in conjunction with liver stiffness could accurately diagnose liver fibrosis in the majority of cases …”
mentioning
confidence: 99%
“…These patients were used as a subset to investigate the kinetics of cell death in association with disease course and outcome. All serum samples were stored according to the standard protocol of our biobank as described earlier . Measurements of serum K18 and cK18 were performed using ELISA kits: M65 EpiDeath® (#10040 Peviva AB) or M30‐Apoptosenses® (#10011 Peviva AB), respectively.…”
Section: Methodsmentioning
confidence: 99%